2016
DOI: 10.7197/cmj.v38i2.5000144674
|View full text |Cite
|
Sign up to set email alerts
|

Molecular view to the effect of centaury oil on wound healing

Abstract: SUMMARYObjective: Centaury oil (the extract of Hypericum perforatum obtained with olive oil) is traditionally used for the treatment of wounds in Turkey. Centaury oil has analgesic and antiinfectious properties beside wound healing effect. There are many studies about the positive effect of this extract on wound healing in literature. But there is no mention about the animal studies that show which pathways are involved in. Method: In our study the effect of centaury oil in early stages (first 7 days) and late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…In addition, they showed that there was no significant difference between the groups in terms of healing and bone formation in the late 30 and 60 days. Çoban Z. et al 30 reported that externally applied St. John's Wort oil had a positive effect in the early period (first 7 days) use, but this effect was not observed in the late period (second 7 days) use. Park J.J. et al 31 concluded that local diode laser irradiation of extraction sockets in diabetic rats promoted early healing, especially for the initial stages of alveolar bone healing in both diabetic and normal rats.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they showed that there was no significant difference between the groups in terms of healing and bone formation in the late 30 and 60 days. Çoban Z. et al 30 reported that externally applied St. John's Wort oil had a positive effect in the early period (first 7 days) use, but this effect was not observed in the late period (second 7 days) use. Park J.J. et al 31 concluded that local diode laser irradiation of extraction sockets in diabetic rats promoted early healing, especially for the initial stages of alveolar bone healing in both diabetic and normal rats.…”
Section: Discussionmentioning
confidence: 99%